Urban regeneration in the context of 'New Urbanisation': the case of Xietang Old Street, Suzhou Industrial Park, China. - Zhong, Sheng (TPR: Town Planning Review, 2020)
Taking an unassuming case in Suzhou, China, this research examines approaches, strategies and outcomes of recent 'exemplary' regeneration practice in China. It answers the question whether the neo-liberal approaches of the old model have been transcended to honour human-centrality and sustainability in line with 'New Urbanisation' principles. Based on surveys, in-depth interviews, a focus group and archival studies, the research finds that the incorporation of social policies into regeneration strategies by the local state, despite achievements in housing and welfare provision, has not helped to transform the top-down and non-participative nature of the old regeneration model.